Comparative virulence of in vitro‐cultured primate‐ and pig‐associated Helicobacter suis strains in a BALB/c mouse and a Mongolian gerbil model. Issue 2 (24th August 2016) - Bosschem, Iris; Flahou, Bram; Bakker, Jaco; Heuvelman, Edwin; Langermans, Jan A.M.; De Bruyne, Ellen; Joosten, Myrthe; Smet, Annemieke; Ducatelle, Richard; Haesebrouck, Freddy
Abstract: Background: Helicobacter suis ( H. suis ) is the most prevalent gastric non‐ H. pylori Helicobacter species in humans. This bacterium mainly colonizes the stomach of pigs, but it has also been detected in the stomach of nonhuman primates. The aim of this study was to obtain better insights into potential differences between pig‐ and primate‐associated H. suis strains in virulence and pathogenesis. Materials and Methods: In vitro‐ isolated H. suis strains obtained from pigs, cynomolgus monkeys ( Macaca fascicularis ), and rhesus monkeys ( Macaca mulatta ) were used for intragastric inoculation of BALB/c mice and Mongolian gerbils. Nine weeks and six months later, samples of the stomach of inoculated and control animals were taken for PCR analysis and histopathological examination. Results: The cynomolgus monkey‐associated H. suis strain only colonized the stomach of mice, but not of Mongolian gerbils. All other H. suis strains colonized the stomach in both rodent models. In all colonized animals, severe gastric inflammation was induced. Gastric lymphoid follicles and destruction of the antral epithelium were observed in infected gerbils, but not in mice. Infection with both pig‐ and primate‐associated H. suis strains evoked a similar marked Th17 response in mice and gerbils, accompanied by increased CXCL‐13 expression levels. Conclusions: Apart from the cynomolgus monkey‐associated strain which was unable of colonizing the stomach of Mongolian gerbils, no substantial differences in virulence were found in rodent models between in vitro‐ cultured pig‐associated, cynomolgus monkey‐associated and rhesus monkey‐associated H. suis strains. The experimental host determines the outcome of the immune response against H. suis infection, rather than the original host.